Is Boiling Bitter Greens a Legacy of Ancient Crete? Contemporary Foraging in the Minoan Refugium of the Lasithi Plateau - Mousaab Alrhmoun; Naji Sulaiman; Shiekh Marifatul Haq; Syed Abidullah; Julia Prakofjewa; Nikos Krigas; Andrea Pieroni; Renata Sõukand (Foods)
Wild greens (WGs) play a significant role in Mediterranean diets (MDs), reflecting botanical and cultural diversities, mainly influenced by a complex conglomerate of local human ecologies. This study investigates local ecological knowledge (LEK) linked to traditional gathering and consumption of WGs in the Lasithi Plateau of eastern Crete, where human genetic studies one decade ago showed very peculiar patterns, hypothesising that the Minoan civilisation took refuge there before it disappeared. A field ethnobotanical study was conducted to document the diversity of WGs and their detailed local culinary uses in the Lasithi area by interviewing 31 study participants. Fifty-nine folk taxa (species and subspecies) were recorded, corresponding to fifty-eight botanical taxa. A quotation index was measured to assess the cultural significance of WGs in the study areas; logistic regression analysis was adopted to understand the impact of sensory classifications of WGs and their local cooking methods. Lasithi’s foraging showed a notable prevalence of bitter-tasting WGs, which play a central role in local cognition and culinary practices. This bitterness aspect of WGs, potentially influenced by cultural preferences and genetic factors, probably suggests a connection to the ancient Lasithi’s inhabitants, i.e., Minoan dietary habits. We found that bitterness is the predominant sensory attribute in Lasithi, characterising 45.76% of the WGs. These findings underscore the complex interplay between local ecologies and biodiversity, LEK, and dietary traditions, highlighting the importance of WGs in understanding the evolution of foraging and plant culinary diversities across the Mediterranean.